MABIT Program as a Cadreization of Ulama in Pesantren: Study of Management - Zainal Berlian (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The position of the ulama for Muslims is crucial in guiding them to the path of goodness. However, the current number of ulama is not proportional to the number of Muslims, coupled with the Covid-19 pandemic, many ulama have died. Therefore, there is a need for a Cadreization of Ulama. This study aims to analyze the Mujahadah and Nursery Program (MABIT) as a Cadreization of Ulama at Pesantren Al-Ittifaqiah in terms of management. The research method used is qualitative. This study concludes that the Mujahadah and Nursery Program (MABIT) for the regeneration of ulama at Pesantren Al-Ittifaqiah is running well and in accordance with the management functions, namely planning, organizing, implementing, and supervising. This program is specifically for students who are tahfiz Al-Qur'an and final level, they are equipped with English language skills, Arabic language, general lessons, and religious lessons.